Reconstructing the invasion history of the bark beetles Orthotomicus erosus and Cyrtogenius luteus (Coleoptera, Curculionidae, Scolytinae) in South America - Stazione, Leonel Daniel (2026)
Global trade and the spread of non-native host plants are driving the introduction of forest insects to new regions, often causing substantial ecological and economic impact. We investigated the invasion history of two non-native pine bark beetles, Orthotomicus erosus and Cyrtogenius luteus, recently established in South America, using mitochondrial DNA to infer source regions, genetic diversity, and invasion pathways. We analyzed specimens from native ranges in Europe and Asia and invaded populations in Argentina and Uruguay. For O. erosus, two genetic clusters were found in its native range, corresponding to western and eastern Eurasian populations. South American populations clustered with the western European lineage and exhibited low genetic diversity, suggesting a single or limited introduction event followed by regional spread. In contrast, C. luteus showed a widespread haplotype shared across all sampled populations pointing China as a possible source region. However, limited sampling within the native range restricted our ability to resolve population structure and assign additional South American haplotypes to specific native sources, while the higher haplotype diversity may reflect multiple introductions. Both species show similar invasion patterns in throughout Argentina and Uruguay, with shared haplotypes between countries indicating a contiguous regional spread, possibly driven by extensive pine plantations and intra-regional trade. Overall, this study highlights the importance of reconstructing invasion histories to inform effective biosecurity and management strategies, particularly given the expected increase in pine-associated insect invasions in South America over the coming decades.